Dampak Perubahan Harga Subsidi (BBM) terhadap Pendapatan Nelayan (Studi Kasus: Dusun Kapuran, Kota Agung, Tanggamus) - Alvina Veronica; Moneyzar Usman (Journal on Education, 2023)
This research aims to analyze the effect of changes in subsidized fuel oil (BBM) prices on fishermen's income. Changes in subsidized fuel prices have a significant impact on fishermen's income, because fuel is one of the main components in fishermen's daily activities to earn a living. The research method used in this research uses a descriptive method with a qualitative approach. The data analysis method in this research uses different test analysis with the Paired Simple Test. The results of the research show that there is a significant influence between changes in subsidized fuel prices on fishermen's income. The results of the analysis show that changes in subsidized fuel prices have a significant impact on fishermen's income, because subsidized fuel prices greatly influence the final operating costs of the ship and the fuel costs for traveling around fishing.